PENGKAJIAN FAKTOR-FAKTOR TINGKAT KEBISINGAN JALAN PERKOTAAN - Rr. Dini Handayani (Jurnal Jalan-Jembatan, 2007)
The studies about the traffic noise and its countermeasures have been done enough, otherwise the studies related to the other factors influencing to the noise level itself have not been conducted. This paper, therefore, reviews the factors affecting to the noise level, likes : traffic parameters, geometric parameters, environment parameters, temperatur parameters. From the first test in Cirebon indicated that temperature parameters has high noise influence. Even though this statement needs the follow up validations. Keywords : Noise level, traffic parameter,weather parameter